Conceptions of the Vernacular Settlement Architecture Orientation: A Literature Study of Research Results - I Kadek Merta Wijaya; Ngakan Ketut Acwin Dwijendra (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2021)
Architectural researchers have conducted researches on the architectural orientation of vernacular settlements, both explicitly and implicitly. The study results differ based on the understanding of the resident's culture of the community, their beliefs, and the context of their settlements. They understand that vernacular settlement architectural orientation results in a different orientation direction in one territory from another in Indonesia. Indonesia is an archipelago country with various tribes spread throughout the Indonesian archipelago. Each ethnic group has a different culture of living, so that the orientation of the Settlement as a form of relationship between tribal people and their